2015
DOI: 10.1371/journal.pone.0118651
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Behaviors, Social Support and Health-Related Quality of Life among Men Who Have Sex with Men and Women (MSMW): A Cross-Sectional Study in Chongqing, China

Abstract: BackgroundHealth-related quality of life (HRQOL) has become commonly used both as a concept and as a field of research. However, little is known about the HRQOL of men who have sex with men and women (MSMW). The aim of this study was to examine HIV-related behaviors, social support, and HRQOL status and explore its predictors among MSMW.MethodsAn anonymous cross-sectional study was conducted by snowball sampling method in 2013. A total of 563 Chinese MSM completed a structured questionnaire. The HRQOL and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…The results of this study were in agreement with a study in China [4]: the QoL of PLWHA was inferior to that of the general population. However, PLWHA reported better QoL when compared with that of family members of PLWHA in Taiwan in our previous study [18], especially in social and environmental domains in Taiwan.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study were in agreement with a study in China [4]: the QoL of PLWHA was inferior to that of the general population. However, PLWHA reported better QoL when compared with that of family members of PLWHA in Taiwan in our previous study [18], especially in social and environmental domains in Taiwan.…”
Section: Discussionsupporting
confidence: 91%
“…These geographical and cultural constructs may influence some MSM to use marriage as a disguise [9]. These men may endure pressures of gay-related stigma, fear of sexual orientation disclosure, as well as carrying a heavy responsibility to support their families [16]. These pressures may partially explain our finding of a higher likelihood of hazardous or binge drinking problems among this subgroup [43].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that 31.2% of the 28,739 MSM in China had ever had sex with a woman [13]. Men who have sex with men and women (MSMW) are less likely to be infected with HIV than MSM-only (MSMO), probably because MSMW are more likely to practice insertive anal (with a man) and virginal intercourse with a woman, which is associated with lower HIV risk compared to receptive anal intercourse with a man [12, 1416]. On the other hand, MSMW are shown not to use condom consistently with female sexual partners [17], which may bridge HIV/STIs to their average-risk female sexual partners [18].…”
Section: Introductionmentioning
confidence: 99%
“…There were cases in some previous study which indicated that certain proportion of MSM may have bisexual behaviors [14]. Thus, among these MSM, it could be reasonable to divide early sexual debut into early VSD and early ASD when investigating the effect of early sexual debut on HIV infection.…”
Section: Introductionmentioning
confidence: 99%